Gambierone and Sodium Channel Specific Bioactivity Are Associated with the Extracellular Metabolite Pool of the Marine Dinoflagellate Coolia palmyrensis - Alexander K. Leynse; Elizabeth M. Mudge; Andrew D. Turner; Benjamin H. Maskrey; Alison Robertson (Marine Drugs, 2023)
Tropical epibenthic dinoflagellate communities produce a plethora of bioactive secondary metabolites, including the toxins ciguatoxins (CTXs) and potentially gambierones, that can contaminate fishes, leading to ciguatera poisoning (CP) when consumed by humans. Many studies have assessed the cellular toxicity of causative dinoflagellate species to better understand the dynamics of CP outbreaks. However, few studies have explored extracellular toxin pools which may also enter the food web, including through alternative and unanticipated routes of exposure. Additionally, the extracellular exhibition of toxins would suggest an ecological function and may prove important to the ecology of the CP-associated dinoflagellate species. In this study, semi-purified extracts obtained from the media of a Coolia palmyrensis strain (DISL57) isolated from the U.S. Virgin Islands were assessed for bioactivity via a sodium channel specific mouse neuroblastoma cell viability assay and associated metabolites evaluated by targeted and non-targeted liquid chromatography tandem and high-resolution mass spectrometry. We found that extracts of C. palmyrensis media exhibit both veratrine enhancing bioactivity and non-specific bioactivity. LC-HR-MS analysis of the same extract fractions identified gambierone and multiple undescribed peaks with mass spectral characteristics suggestive of structural similarities to polyether compounds. These findings implicate C. palmyrensis as a potential contributor to CP and highlight extracellular toxin pools as a potentially significant source of toxins that may enter the food web through multiple exposure pathways.